2020
DOI: 10.3390/foods9121839
|View full text |Cite
|
Sign up to set email alerts
|

Content and Dietary Exposure Assessment of Toxic Elements in Infant Formulas from the Chinese Market

Abstract: In this study, the content of chromium (Cr), arsenic (As), cadmium (Cd) and lead (Pb) in domestic and imported infant formulas from Beijing, China were analyzed using inductively coupled plasma mass spectrometry. The content of Cr, As, Cd and Pb was 2.51–83.80, 0.89–7.87, 0.13–3.58 and 0.36–5.57 μg/kg, respectively. Even though there were no significant differences in toxic elements content between domestic and imported infant formulas, Cd content was slightly lower in domestic samples. The estimated daily int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
5
8
3
Order By: Relevance
“…Previous studies suggested that rice plants highly accumulate As compared to other grains such as wheat and barley (Rahman & Hasegawa, 2011;Williams et al, 2007). Many baby food products including cereals, puffs, and biscuits are made mainly of rice because of its nutrients Current levels of Cd tested in baby foods were consistent with previous reports (Table 5) in Saudi Arabia, Turkey, Germany, Poland, and China (Başaran, 2022;Bundesinstitut für Risikobewertung, 2018;Khalifa & Ahmad, 2010;Mania et al, 2015;Su et al, 2020). Cd contents in infant formula analyzed in this study were lower than the contents observed in Italy and Egypt (Bargellini et al, 2018;Ghuniem et al, 2020).…”
Section: Occurrence Datasupporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies suggested that rice plants highly accumulate As compared to other grains such as wheat and barley (Rahman & Hasegawa, 2011;Williams et al, 2007). Many baby food products including cereals, puffs, and biscuits are made mainly of rice because of its nutrients Current levels of Cd tested in baby foods were consistent with previous reports (Table 5) in Saudi Arabia, Turkey, Germany, Poland, and China (Başaran, 2022;Bundesinstitut für Risikobewertung, 2018;Khalifa & Ahmad, 2010;Mania et al, 2015;Su et al, 2020). Cd contents in infant formula analyzed in this study were lower than the contents observed in Italy and Egypt (Bargellini et al, 2018;Ghuniem et al, 2020).…”
Section: Occurrence Datasupporting
confidence: 86%
“…Similar results for all infant age groups were observed in the United States (0.00 μg/kg bw/day), Poland (0.05-0.76 μg/kg bw/day), Turkey (0.03 μg/kg bw/day), China (0.01 μg/kg bw/day), and Italy (0.02 μg/kg bw/day) (Bargellini et al, 2018;Başaran, 2022;Gardener et al, 2019;Mania et al, 2015;Su et al, 2020). Similar to As, the presence of Cd, even in scarce amounts, in infant food products is concerning.…”
Section: Risk Assessment: Daily Intake Estimation Target Hazard Quoti...supporting
confidence: 80%
See 1 more Smart Citation
“…For example, a study in the field conducted in 2018 [ 30 ] on some infant formulas sold in Ethiopia reported a range concentration of Zn and Pb equal to 27.9–71.5 µg g −1 and <LOD–0.103 µg g −1 , respectively, while Cd concentrations were always <LOD. These differences in elemental concentrations all over the countries were also evidenced by other researches in China and Pakistan [ 46 , 47 ]. Likewise, similarities between the elemental concentrations found in formulas marketed in EU countries and differences with the levels reported for the formulas sold in countries outside EU are due to differences in raw materials, processing and packaging, and regulations.…”
Section: Discussionsupporting
confidence: 71%
“… Here, RfD is the oral toxicity reference dose of heavy metals/nitrate (mg/kg/day). RfD values for Al, iAs, Cd, Pb, and nitrate are 1.0, 3.0 × 10 −4 , 1.0 × 10 −3 , 4.0 × 10 −4 , and 7.0 mg/kg/day, respectively (ATSDR, 2013; Su et al, 2020; US EPA, 2015). When HQ ≤1, the pickle beverages could be safe for the consumed population, while at HQ > 1, there is a potential noncarcinogenic health risk (Fathabad et al, 2018; US EPA, 2000).…”
Section: Noncarcinogenic Risk Assessmentmentioning
confidence: 99%